AVALIAÇÃO DA TOLERÂNCIA AO ALUMÍNIO ATRAVÉS DA SOLUÇÃO MÍNIMA EM DIFERENTES GERMOPLASMAS DE MILHO. - Coelho, Caroline de Jesus (2011)
The aluminum toxicity has limited the potential yield in most crops, especially damage caused by the root system as inhibiting the growth, elongation and absorption of nutrients. The objectives were to standardize the concentration of aluminum and exposure of the roots of seedlings in minimal solution (Ca2+ + Al3+) and subsequently characterize the genetic variability of tolerance to the element in different germplasm (hybrids and landraces). The experiments of the approach of minimal solution in DBC were implanted with three replications. The treatments were arranged in a split plot where the plot studied the effect of doses of Al3+ (0, 2, 4 and 6 mg L-1) and the subplot effect of hybrids, which were exposed for a period of 96 h (1 and 2 experiments) and 48 h (experiment 3). The variables analyzed were the DIF1 (root net growth), DIF2 (root final growth) and their relative differences (DIFR1 and DIFR2). The variables analyzed were effective for assessing the tolerance / sensitivity to aluminum in minimal solution. The results revealed dramatic decline in root growth of all the hybrids with increasing doses of Al3+, based on the square root regression model. The starting dose of 4 mg L-1 the damage is so pronounced that virtually paralyzed the root growth when exposed for 96 h. On the other hand, when the hybrids were exposed for 48 h and the differences in tolerance or sensitivity were seen. In this sense, we standardized for the other experiments (characterization of germplasm), the minimal solution containing 4 mg L-1 + Al3+ + 40 mg L-1 Ca2+ implanted in the DBC with three replications. Germplasm in hybrid maize were carried out two experiments (48 and 96 h of exposure) with a total of 52 hybrids and germplasm experiment with landraces, with 54 treatments: 50 landraces + 4 hybrid control (48 h exposure). The genotypes were evaluated for the same variables as well as classified for the tolerance on the aluminum (ITRAl). Germplasm in hybrid, the analysis showed genetic variability for tolerance or sensitivity to, and Al+3. In general, the exposure period of 96 h significantly reduced the growth / root regrowth. The majority of the hybrids (35) showed a reduction in the value of ITRAl due to the increase of the exposure period, while 15 hybrids responded with an increase in this index. The evaluation of landraces showed very high values of growth / root regrowth as well as a predominance of genotypes (50%) classified as ITRAl ≥ 4, are considered excellent sources of aluminum tolerance. Featured very positive for the landrace Dente de Ouro 2 that showed a value of more than control ITRAl tolerant H 44. Estimates of genetic parameters in two maize germplasm showed high levels of genetic variance and heritability coefficients. These indices indicate very favorable conditions for development and selection of populations improved with increase in frequency of alleles of aluminum tolerance.